“Efectos del trinchado de raíces de banano (Musa AAA) sobre la masa radical y la densidad poblacional de nemátodos”. - Cando Tuarez, Cesar Gabriel (2019)
VIII. SUMMARY The banana in Ecuador is one of the most important crops in terms of generating foreign exchange and jobs, pests and diseases are one of the main problems in productivity, among these pests the phytoparasitic nematodes are the most important after the Black sigatoka. The present investigation was developed in the Hcda Alejandra located at km 22.5 of the San Juan-Babahoyo road, the objectives of this research were to determine the effect of the carving of banana roots on the radical mass and population density of nematodes. The work was designed with five treatments and five repetitions of carving. The treatments were composed of carving numbers and by arrangement with respect to the daughter plant (1.50-2.0 m height), these being: 1) two frontal carving, 2) three frontal carving, 3) two lateral carving, 4) three lateral carving, 5) control without carving. The evaluation of the treatments was carried out at 30, 60 and 90 days after carving. The total weight of roots was evaluated by daughter plant, percentage of healthy roots, and population density of nematodes in roots and soil. The carving of banana roots does not present significant effects in the increase of the radical mass of banana roots (total weight of roots), percentage of healthy roots, and reduction of the population density of nematodes. Numerically, with two frontal carving of roots, a little more root mass and percentage of healthy roots were obtained than with the other three forms of carving. The treatment of two lateral carcasses against the banana child had a lower population of Meloidogyne spp. and Helicotylenchus multicinctus. Keywords: carving, root mass, nematodes population densities, roots lesion nematodes, root-knot nematodes.